2008
DOI: 10.1007/s12306-008-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of interdigital Morton’s neuroma

Abstract: The Authors present their experience in the surgical treatment of Morton's neuroma via a dorsal approach. The assessed results have been very good in terms of a clear clinical improvement and no recurrences in all the treated cases. The histological examination carried out on all the removed samples have shown that the thickening of the nerve first occurs due to perineural fibrosis and successively associated with sclerohyalinosis of the tissue, which is in line with the already existing literature reports. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…In line with this, 83% of patients in our case series study were female. Our study found that the average age at which the neuroma appears in patients was 56±13.96 years, which concurs with a study by Di Caprio and colleagues14,16,17 (range 45 to 60 y).…”
Section: Discussionsupporting
confidence: 93%
“…In line with this, 83% of patients in our case series study were female. Our study found that the average age at which the neuroma appears in patients was 56±13.96 years, which concurs with a study by Di Caprio and colleagues14,16,17 (range 45 to 60 y).…”
Section: Discussionsupporting
confidence: 93%
“…Most commonly reported were the results of surgical neurectomy. 66-71 Following this procedure, complete pain relief was seen in up to 68%, with better results reported when used in combination with transposition of the transected proximal nerve stump. 66 Patient satisfaction rates were generally reported as being higher, but this may reflect the variety of unvalidated outcomes measures used to determine this.…”
Section: Discussionmentioning
confidence: 99%
“…This is a very common and typical report from those suffering with PDN. 11,13,15,20 100% of the patients in this study reported substantial decreases in their VAS readings, with 81% reporting being entirely pain-free by the conclusion of their 6 treatments. Where the clinician felt there remained a loss of normal motion in the affected joint, the manipulation was repeated even if the patient reported a VAS score of zero.…”
Section: Discussionmentioning
confidence: 69%
“…7,[11][12][13] The clinical presentation, positive clinical tests, and a good history are usually sufficient to make an accurate diagnosis. 5,12 Patients who present with this condition will commonly complain of a burning or lancing pain, with or without accompanying paresthesia in the ball of the foot which is relieved by rest and the removal of footwear.…”
Section: Introductionmentioning
confidence: 99%